Molecular docking study of the interactions between Plasmodium falciparum lactate dehydrogenase and 4-aminoquinoline hybrids - Nur Hanis Zakaria; Lam, Kok Wai; Nurul Izzaty Hassan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Malaria is a potentially deadly disease with many anti-malarial drugs have been rendered ineffective due to Plasmodium falciparum resistance concern. Plasmodium falciparum lactate dehydrogenase (PfLDH) enzyme is a crucial malaria parasite enzyme involved in the glycolytic pathway, thus, has been considered as a potential molecular target. Initially, molecular docking was performed using AutoDock Vina, Molegro Virtual Docker, and CDOCKER software to investigate the molecular interactions of 4-aminoquinoline antimalarial hybrids compounds with PfLDH enzyme. All ten 4-aminoquinoline hybrids derivatives docked to the PfLDH binding site. The results showed that these compounds exhibited either comparable or higher binding affinity than the reference drug chloroquine, amodiaquine, and hydroxychloroquine. Visually, some of the compounds possessed functional binding interactions, possibly due to their similar structural conformation and binding interactions of chloroquine in the binding site. Apart from that, the docking results also suggest that these compounds potentially promote additional hydrogen-bonding interactions with the residues in the binding site. Interestingly, the compounds also predicted to interact with essential PHE52, VAL26, ILE54, ILE119, and ALA98 residues, which are required to act as a competitive inhibitor for this glycolytic enzyme.